Secondary Malignancy Risk Following Proton Radiation Therapy - Eaton, Bree R.; MacDonald, Shannon M.; Yock, Torunn I.; Tarbell, Nancy J. (Frontiers in Oncology, 2015)
Radiation induced secondary malignancies are a significant, yet uncommon cause of morbidity and mortality among cancer survivors. Secondary malignancy risk is dependent upon multiple factors including patient age, the biological and genetic predisposition of the individual, the volume and location of tissue irradiated, and the dose of radiation received. Proton therapy is an advanced particle therapy with unique dosimetric properties resulting in reduced entrance dose and minimal to no exit dose when compared with standard photon radiation therapy. Multiple dosimetric studies in varying cancer subtypes have demonstrated that proton therapy enables the delivery of adequate target volume coverage with reduced integral dose delivered to surrounding tissues, and modeling studies taking into account dosimetry and radiation cell biology have estimated a significantly reduced risk of radiation induced secondary malignancy with proton therapy. Clinical data is emerging supporting the lower incidence of secondary malignancies after proton therapy compared with historical photon data, though longer follow-up in proton treated cohorts is awaited. This article reviews the current dosimetric and clinical literature evaluating the incidence of and risk factors associated with radiation induced secondary malignancy following proton therapy.